The Chymase Mouse Mast Cell Protease-4 Regulates Intestinal Cytokine Expression in Mature Adult Mice Infected with Giardia intestinalis - Zhiqiang Li; Dimitra Peirasmaki; Staffan Svärd; Magnus Åbrink (Cells, 2020)
Mast cells have been shown to affect the control of infections with the protozoan parasite Giardia intestinalis. Recently, we demonstrated that Giardia excretory-secretory proteins inhibited the activity of the connective tissue mast cell-specific protease chymase. To study the potential role of the chymase mouse mast cell protease (mMCP)-4 during infections with Giardia, mMCP-4+/+ and mMCP-4−/− littermate mice were gavage-infected with G. intestinalis trophozoites of the human assemblage B isolate GS. No significant changes in weight gain was observed in infected young (≈10 weeks old) mMCP-4−/− and mMCP-4+/+ littermate mice. In contrast, infections of mature adult mice (>18 weeks old) caused significant weight loss as compared to uninfected control mice. We detected a more rapid weight loss in mMCP-4−/− mice as compared to littermate mMCP-4+/+ mice. Submucosal mast cell and granulocyte counts in jejunum increased in the infected adult mMCP-4−/− and mMCP-4+/+ mice. This increase was correlated with an augmented intestinal trypsin-like and chymotrypsin-like activity, but the myeloperoxidase activity was constant. Infected mice showed a significantly lower intestinal neutrophil elastase (NE) activity, and in vitro, soluble Giardia proteins inhibited human recombinant NE. Serum levels of IL-6 were significantly increased eight and 13 days post infection (dpi), while intestinal IL-6 levels showed a trend to significant increase 8 dpi. Strikingly, the lack of mMCP-4 resulted in significantly less intestinal transcriptional upregulation of IL-6, TNF-α, IL-25, CXCL2, IL-2, IL-4, IL-5, and IL-10 in the Giardia-infected mature adult mice, suggesting that chymase may play a regulatory role in intestinal cytokine responses.